Measuring customer satisfaction: a study of the Swedish real estate industry. Issue 4 (15th August 2016) - Palm, Peter
Abstract : Purpose: The aim is to identify the strategies of formal customer evaluations and the use of Satisfied Customer Index in the Swedish commercial real estate industry. Design/methodology/approach: This research is based on an inventory of twenty-four commercial real estate companies use of formal customer evaluations and an analysis of fifteen interviews with top-level managers in the Swedish commercial real estate sector. Findings: Only half of the companies included in the study conduct formal evaluations, although they are considered to work customer oriented. Two different strategies for using formal evaluations is, for improvement work and for signalling quality. One proposed explanation to why only half of the companies conduct formal evaluations is the possibility that the official Swedish Real Estate Barometer is not sufficient if the company would like to use the result for organisational development. There are instead indications that this Barometer mainly is used in publicity and marketing purpose, to signal quality Research limitations/implications: The research in this paper is limited to Swedish commercial real estate sector. But, the overall strategies for conducting formal evaluations should be applicable in general. Practical implications: The insight the paper provides regarding how the industry perceive the Swedish Real Estate Barometer gives direct implications of improvements of the barometer. Originality/value: It provides an insight regarding the use of formal customer evaluations and a proposition of how the Swedish Real Estate Barometer could be changed to better support and fulfil the aim of being a barometer for benchmarking.